2018
DOI: 10.18632/oncotarget.24380
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29b reverses oxaliplatin-resistance in colorectal cancer by targeting SIRT1

Abstract: Oxaliplatin is a commonly used chemotherapeutic drug for the treatment of advanced colorectal cancer. However, acquired drug resistance against oxaliplatin remains a major obstacle for efficient use of it, and mechanisms underlying oxaliplatin resistance are still required to be explored. In the present study, we exposed colorectal cancer cell line SW480 to oxaliplatin for a long time to obtain oxaliplatin-resistant colorectal cancer cell model (OR-SW480). We found that intracellular expression of miR-29b was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Through the growth inhibition assay, we found that the IC50 value of the control group was 3.068 times higher than that of the SPIB overexpression group, indicating that the high expression of SPIB could increase the sensitivity of CRC cells to oxaliplatin. Since the activation of JNK can promote oxaliplatin induced apoptosis [16], we believe that the high expression of SPIB induces the sensitivity of CRC cells to oxaliplatin by activating the JNK pathway. 5-FU is a commonly used chemotherapy drug in tumor therapy [17], which mainly targets at the S phase of cell cycle and other phases to play an anti-tumor role [18].…”
Section: Discussionmentioning
confidence: 98%
“…Through the growth inhibition assay, we found that the IC50 value of the control group was 3.068 times higher than that of the SPIB overexpression group, indicating that the high expression of SPIB could increase the sensitivity of CRC cells to oxaliplatin. Since the activation of JNK can promote oxaliplatin induced apoptosis [16], we believe that the high expression of SPIB induces the sensitivity of CRC cells to oxaliplatin by activating the JNK pathway. 5-FU is a commonly used chemotherapy drug in tumor therapy [17], which mainly targets at the S phase of cell cycle and other phases to play an anti-tumor role [18].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, miR-29b is considered as a tumor marker for the prognosis of CRC. In previous studies on tumor chemotherapy drug resistance, miR-29b was found to reverse Oxa resistance of CRC cells by targeting the SIRT1/ROS/JNK pathway [ 46 ], moreover, it can also target FOLR1 to inhibit cell growth of colon cancer cells and increases cell sensitivity to Oxa [ 47 ]. Our experimental results further complement these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29b has been documented to negatively affect tumorigenesis and cancer progression by regulating cell proliferation, survival, and metastasis 28 , Whilst overexpression of miR-29b can also inhibit tumorigenesis 35 and angiogenesis 36 - 38 . Moreover, miR-29b can reverse drug resistance in ovarian cancer 39 , 40 and colorectal cancer 41 , as well as radioresistance in cervical cancer 42 . In this study, we found that overexpression of miR-29b-3p reduced cell viability, suppressed cell proliferation, and decreased colony formation, resulting in increased sensitivity of LNCaP cells to X-rays irradiation.…”
Section: Discussionmentioning
confidence: 99%